2018
DOI: 10.1155/2018/7356546
|View full text |Cite
|
Sign up to set email alerts
|

Correlation Analysis between Traditional Chinese Medicine Syndromes and Gastrointestinal Bleeding after Percutaneous Coronary Intervention

Abstract: Objective To explore the characters of traditional Chinese medicine (TCM) syndromes after percutaneous coronary intervention (PCI) and to provide syndrome study theoretical evidence for TCM differentiation treatment after PCI through retrospective study. Methods Patients with coronary heart disease (CHD) who underwent PCI in Cardiovascular Intervention Center of Wangjing Hospital during Dec. 2012 to Dec. 2014 and met the inclusion criteria were enrolled. Retrospective study was then conducted based on patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 14 publications
0
7
0
Order By: Relevance
“…10 Qi de ciency and blood stasis syndrome has been reported to have a correlation with the bleeding after receiving percutaneous coronary intervention. 11 A study has shown that Qi-de ciency is associated with cancer related fatigue. 12 In addition to the association with disorders, TCM syndrome differentiation has been demonstrated to correlate with many measureable clinical indexes in modern medicine in disease setting.…”
Section: Discussionmentioning
confidence: 99%
“…10 Qi de ciency and blood stasis syndrome has been reported to have a correlation with the bleeding after receiving percutaneous coronary intervention. 11 A study has shown that Qi-de ciency is associated with cancer related fatigue. 12 In addition to the association with disorders, TCM syndrome differentiation has been demonstrated to correlate with many measureable clinical indexes in modern medicine in disease setting.…”
Section: Discussionmentioning
confidence: 99%
“…Diagnosis standard of CHD refers to “nomenclature and diagnosis criteria of ischemic heart disease” which is established by the Joint International Society and Federation of Cardiology/World Health Organization Task Force on Standardization of Clinical Nomenclature (Nomenclature and criteria for diagnosis of ischemic heart disease, 1979). The syndrome was identified by three chief physicians, according to “criteria for TCM syndrome differentiation of patients with coronary heart disease” (Subcommittee of Cardiovascular Diseases of China Society of Integrated Traditional Chinese, and Western Medicine, 1991).…”
Section: Methodsmentioning
confidence: 99%
“…Research indicated the incidence of gastrointestinal bleeding following PCI as being 2.3%, while the incidence of bleeding in high-risk groups was as high as 12%. 2 Hemorrhaging is related to the use of DAPT, and aspirin can directly damage the epithelial cells of gastrointestinal mucosa. 3 Furthermore, clopidogrel may delay the healing of gastric mucosal injuries.…”
Section: Introductionmentioning
confidence: 99%